2016
DOI: 10.1007/978-3-319-46963-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measures of News Personalization in Google News

Abstract: Search engines and social media keep trace of profile-and behavioral-based distinct signals of their users, to provide them personalized and recommended content. Here, we focus on the level of web search personalization, to estimate the risk of trapping the user into so called Filter Bubbles. Our experimentation has been carried out on news, specifically investigating the Google News platform. Our results are in line with existing literature and call for further analyses on which kind of users are the target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 9 publications
0
5
0
4
Order By: Relevance
“…They show that prior suicide-harmful, suicide-preventative or suicide-unrelated search behaviour had no impact on the display of a helpline SERP feature. Regarding Google News, Haim et al (2018) show that untrained accounts received approximately the same news articles as accounts trained according to different types of news users (also see Cozza et al 2016; but some support for personalisation found by Le et al 2019). In general, these algorithm audits suggest that algorithmic curation in information search is, at most, limited.…”
Section: Algorithmic Curationmentioning
confidence: 75%
“…They show that prior suicide-harmful, suicide-preventative or suicide-unrelated search behaviour had no impact on the display of a helpline SERP feature. Regarding Google News, Haim et al (2018) show that untrained accounts received approximately the same news articles as accounts trained according to different types of news users (also see Cozza et al 2016; but some support for personalisation found by Le et al 2019). In general, these algorithm audits suggest that algorithmic curation in information search is, at most, limited.…”
Section: Algorithmic Curationmentioning
confidence: 75%
“…News, images and video search results have also been subject to virtual agent-based auditing. Cozza et al [ 13 ] found personalisation effects for the recommendation section of Google News, but not for the general news section. In line with this, Haim et al [ 14 ] found that only 2.5% of the overall sample of Google News results ( N = 1200) were exclusive to four constructed agents based on archetypical life standards and media usage.…”
Section: Related Workmentioning
confidence: 99%
“…One of the most studied platforms are web search engines -almost half of the auditing works reviewed by Bandy [5] were focused on Google alone -as a plethora of concerns have been raised about representation, biases, copyrights, transparency and discrepancies in their outputs. Research has analysed issues in areas such as elections [6][7][8][9][10][11], filter bubbles [12][13][14][15][16][17], personalised results [18,19], gender and race biases [20][21][22], health [23][24][25], source concentration [10,[26][27][28][29], misinformation [30], historical information [31,32] and dependency on user-generated content [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, concerns about the possible negative effects of personalised online services have led to efforts to quantify their degree of personalisation. For example, personalisation in web search as well as online news has been measured by using similarity ratios (Cozza et al, 2016; Dos Santos et al, 2020; Hannák et al, 2017; Krafft et al, 2019; Le et al, 2019; Puschmann, 2018; Salehi et al, 2015). Similarity ratios have also been applied to measuring targeted online advertising (Balebako et al, 2012; Guha et al, 2010).…”
Section: A Novel Metric: the Capimentioning
confidence: 99%